EFEKTIVITAS TERAPI MUROTAL AL-QURAN SURAT AR–RAHMAN TERHADAP PENURUNAN INTENSITAS NYERI PADA IBU BERSALIN KALA I FASE AKTIF DI TPMB LILIK MINDAJATININGTYAS KABUPATEN JOMBANG: Effectiveness Of Ar-Rahman Surat Al-Quran Recitation Therapy On Reducing Pain Intensity In Women In The Active Phase Of The First Stage At Tpmb Lilik Mindajatiningtyas, Jombang Regency - Kustanti, Hani Dwi (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2025)
Introduction : Labor pain is a subjective experience of physical sensations associated with uterine contractions, cervical dilatation and effacement, and fetal descent during labour. Physiological responses to pain include increased blood pressure, pulse, breathing, sweating, pupil diameter, and muscle tension. The aim of this study was the effect of giving Al-Qur'an Surah Ar-Rahman Murotal Therapy on Reducing Pain Intensity in Mothers in the Active Phase I of Labor at TPMB Lilik Mindajatiningtyas, Jombang Regency. Methods: Quasi-experimental research design using non-equivalent control group pretest and posttest. Population All maternal patients in the first active phase of labor at TPMB Lilik Mindajatiningtyas Jombang, from June to August 2023. The sample consisted of 30 patients using an accidental sample. Data collection by observation. The independent variable of murattal al-Quran therapy, the dependent variable Maternal pain in the active phase I, used the Wilcoxon Rank test and the Mann Whitney test. Results: Based on the results of the study on the control group, it was found that the intensity of pain before being given Al-Qur'an Surah Ar-Rahman Murotal Therapy to Mothers in the First Active Phase of Labor (73.3%) as many as 11 respondents with moderate pain. Meanwhile, after being given Al-Qur'an Surah Ar-Rahman Murotal Therapy to the Mothers in the Active Phase I, almost all of them (86.7%) as many as 13 respondents with moderate pain. Whereas in the experimental group, the intensity of pain before being given Murotal Al-Qur'an Surah Ar-Rahman therapy to the Mothers of the First Phase of Active Phase was mostly (66.7%) as many as 10 respondents with moderate pain. Meanwhile, after being given Al-Qur'an Surah Ar-Rahman Murotal therapy to Maternity Mothers in the Active Phase I, almost half (46.7%) were 7 respondents with mild pain and moderate pain. Analysis: Statistical test using Mann Whitney obtained a value of P = 0.026 (? <0.05). Thus, it was concluded that there were differences in changes in pain in the control group and the intervention group after being given Al-Qur'an Surah Ar-Rahman Murotal Therapy for Mothers in the Active Phase I of Labor at TPMB Lilik Mindajatiningtyas, Jombang Regency in 2023. Conclusion: Based on the above it can be concluded that it is concluded that there is an effect of Al-Qur'an Surah Ar-Rahman Murotal Therapy on reducing pain intensity in Mothers in the Active Phase I in TPMB Lilik Mindajatiningtyas, Jombang Regency in 2023